Quality of Life: A Longitudinal Analysis of Correlates of Morale in Old Age. (2004) - Shahtahmasebi, Said
Abstract : This paper examines recurrent continuous morale in old age within a statistical modelling paradigm. The Anglicised Philadelphia Geriatric Centre Morale Scale was used as a small component of a major longitudinal study of old age in rural North Wales, U.K. The literature review and cross-sectional analysis of morale in old age is published elsewhere. This paper deals with the aspect of the longitudinal analysis of morale in old age. The proposed statistical modelling relates recurrent morale to a set of explanatory variables that includes subjective as well as objective measures. In order to assess the degree to which explanatory variables influence morale, an adequate statistical model must handle the possibility that substantial variation between respondents will be due to unmeasured and potentially unmeasurable variables (residual heterogeneity), multicollinearity, and past behaviour effect. These applications are illustrated using morale in old age from the North Wales Longitudinal Study Old Age. The results suggested a strong presence of heterogeneity effect, i.e., current levels of morale appear to be individual specific and independent of its previous levels.